Nutritional Lipids and Mucosal Inflammation. Issue 5 (26th August 2020) - Wawrzyniak, Paulina; Noureddine, Nazek; Wawrzyniak, Marcin; Lucchinetti, Eliana; Krämer, Stefanie D.; Rogler, Gerhard; Zaugg, Michael; Hersberger, Martin
Abstract: Inflammatory bowel disease (IBD) is characterized by chronic relapsing inflammation in the intestine. Given their role in regulation of inflammation, long‐chain n‐3 polyunsaturated fatty acids (PUFAs) represent a potential supplementary therapeutic approach to current drug regimens used for IBD. Mechanistically, there is ample evidence for an anti‐inflammatory and pro‐resolution effect of long‐chain n‐3 PUFAs after they incorporate into cell membrane phospholipids. They disrupt membrane rafts and when released from the membrane suppress inflammatory signaling by activating PPAR‐γ and free fatty acid receptor 4; furthermore, they shift the lipid mediator profile from pro‐inflammatory eicosanoids to specialized pro‐resolving mediators. The allocation of long‐chain n‐3 PUFAs also leads to a higher microbiome diversity in the gut, increases short‐chain fatty acid‐producing bacteria, and improves intestinal barrier function by sealing epithelial tight junctions. In line with these mechanistic studies, most epidemiological studies support a beneficial effect of long‐chain n‐3 PUFAs intake on reducing the incidence of IBD. However, the results from intervention trials on the prevention of relapse in IBD patients show no or only a marginal effect of long‐chain n‐3 PUFAs supplementation. In light of the current literature, international recommendations are supported that adequate diet‐derived n‐3 PUFAs might be beneficial in maintaining remission in IBD patients. Abstract : Fish oils contain n‐3 polyunsaturated fatty acids (PUFAs) which are a potential supplementary therapeutic approach to current drug regimens used for inflammatory bowel disease (IBD). The effect of n‐3 PUFAs on gut inflammation and the microbiome is summarized, and also summarized are the epidemiological and clinical studies in humans that investigated the role of n‐3 PUFAs in IBD.